PSXIII-35 Relationship between early gestation maternal plasma progesterone concentrations and within-litter birth weight variation from Yorkshire sired litters. (5th December 2019) - Miles, Jeremy; Rempel, Lea A; Cushman, Robert; Lents, Clay
Abstract: The objective of this study was to determine if maternal plasma progesterone (P4) during early gestation influences within-litter birth weight variation in pigs. White crossbred females (n = 589) of mixed parity (1–4) were bred at standing estrus designated as day 0 of pregnancy and again 24 h later using single-sire semen from commercial Yorkshire genetics. At day 7 of pregnancy, a single blood sample from each female was collected, processed for plasma and P4 was analyzed using a validated RIA for swine. Dams were allowed to farrow under normal management procedures and standard litter statistics (e.g., number born alive, piglet birth weight, etc.) were recorded. Within-litter birth weight variation (BWV) was determined for each litter using the coefficient of variation of birth weight. Pearson correlation analysis illustrated there was a low (r = 0.0967) but significant (P = 0.0191) positive correlation between P4 and BWV. Linear regression demonstrated that for every ng/ml increase in P4 during early gestation, BWV increased 0.11 ± 0.04%. For this population, the mean BWV was 19.4% with a SD of 7.8%. When analyzing P4 concentrations from extreme groups of females with high or low BWV [i.e. females with 1 SD above, high group (>27.2%; n = 100); or below, low group (< 11.6%; n = 106) the mean BWV] by GLM procedures, high BWV group females had increased (P = 0.0473) concentrations of P4 during early gestation compared to low BWV group (13.9 ± 1.4 vs. 9.0 ± 1.7 ng/ml, respectively). These data demonstrate a positive relationship for early gestation plasma P4 concentrations with greater BWV; thereby, illustrating that high concentrations of P4 during early gestation influence within-litter birth weight variation in pigs. USDA is an equal opportunity provider and employer.